2020
DOI: 10.1038/s41563-020-0703-y
|View full text |Cite
|
Sign up to set email alerts
|

A biohybrid synapse with neurotransmitter-mediated plasticity

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
257
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(281 citation statements)
references
References 36 publications
2
257
0
Order By: Relevance
“…31,50 Recently, it was demonstrated that biological cells can directly modulate the long-term state of organic neuromorphic devices depending on the amount of neurotransmitter released. 51 This work shows how integrated adaptive connections can work for hybrid biological/neuromorphic systems.…”
Section: Integration With Biologymentioning
confidence: 97%
“…31,50 Recently, it was demonstrated that biological cells can directly modulate the long-term state of organic neuromorphic devices depending on the amount of neurotransmitter released. 51 This work shows how integrated adaptive connections can work for hybrid biological/neuromorphic systems.…”
Section: Integration With Biologymentioning
confidence: 97%
“…[ 8,16–19 ] Recent years have seen growing research activities in the field of organic memristors, [ 20,21 ] and their performance has been demonstrated to be comparable to biological synapses, [ 12,22 ] hence highly promising for processing biological signals. [ 23,24 ] Importantly, the operational stability of organic memristors can rival that of inorganic memristors. [ 25–27 ]…”
Section: Figurementioning
confidence: 99%
“…Recently, a path toward scalable organic-based networks has been shown for parallel programming/training, by combining electrochemical organic neuromorphic devices with an ionic diode (memristive switching device) as the access device. 67 Of particular interest for future applications, is the use of such ANNs in a more generic neuromorphic system, a hybrid agent, [78][79][80][81] for local signal processing in bioelectronics. 18 Indeed, concepts of local processing and feature extraction can minimize data transfer from the acquisition site to peripheral electronics, thereby allowing for fully autonomous applications in bioelectronics.…”
Section: Organic Devices For Brain-inspired Computing Artificial Implmentioning
confidence: 99%